A Qualitative Analysis of Organizational Changes That Were Steered by the Results-Based Finance Program in Zimbabwe - Artwell Manyera (Polish Political Science Yearbook)
The study analyzes qualitatively the organizational changes steered by the Results Based Finance program (RBF) in Zimbabwe using a case study of Marondera and Zvishavane districts. The research findings are based on the key informants’ responses from focus group discussions and in-depth interviews. Some qualitative information was sourced from field observations and institutional RBF reports. It was established that significant organizational changes had been driven since the launch of the RBF program in the Marondera and Zvishavane districts in 2011. The changes were categorically stipulated in the RBF program implementation manual. The responsibilities of executive members at both the district and provincial levels expanded. Some of the changes include the introduction of District Steering Committees (DSCs) and Community Based Organizations (CBOs). Furthermore, Health Centre Committees (HCCs) were engaged in implementing the RBF program. Nevertheless, the organizational changes were not augmented by capacity building and empowerment amongst the CBOs, HCCs, and DSCs. Moreover, there was no adequate material and financial support for the new changes. Thus, there is a need to reinforce the organizational changes of health financing programs through robust capacity building among stakeholders engaged.